2009
DOI: 10.1097/aog.0b013e31819fe844
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Risk of Mortality in Women With Vaginal Cancer

Abstract: Objective-To estimate the current effect of demographics, pathology, and treatment on mortality among women with vaginal cancer.Methods-Using data from 17 population-based cancer registries that participate in the Surveillance, Epidemiology, and End Results (SEER) program, 2,149 women diagnosed with primary vaginal cancer between 1990 to 2004 were identified. The association between various demographic factors, tumor characteristics, and treatments and risk of vaginal cancer mortality were evaluated using Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 24 publications
2
59
1
4
Order By: Relevance
“…Shah et al [30] reported a significantly higher risk of death for patients aged 70-79 years and aged 80-89 years compared with those aged 50-59 years [30]. In our study, women aged 70 years or older had a 1.696-fold higher risk of death compared with younger women.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Shah et al [30] reported a significantly higher risk of death for patients aged 70-79 years and aged 80-89 years compared with those aged 50-59 years [30]. In our study, women aged 70 years or older had a 1.696-fold higher risk of death compared with younger women.…”
Section: Discussionsupporting
confidence: 54%
“…Older age at presentation was a predictor of poor clinical outcome in most papers [6,20,[28][29][30]. Shah et al [30] reported a significantly higher risk of death for patients aged 70-79 years and aged 80-89 years compared with those aged 50-59 years [30].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates have been found to be very high for post-menopausal women, ranging between 2.08/100,000 for 60-to 69-year-old women and 4.43/100,000 for 80-to 89-year-old women (11). The average age at first diagnosis was found to be 57 years (7).…”
Section: Discussionmentioning
confidence: 96%
“…The average age at first diagnosis was found to be 57 years (7). Socioeconomic factors such as level of education, income and poverty seem to have no influence on incidence rates (11).…”
Section: Discussionmentioning
confidence: 99%
“…A single institution review suggested that tumor stage, site, and size were all important prognostic factors [24]. Shah et al [25] also reported stage, tumor size, histology, and treatment modality significantly affected a woman's risk of mortality from vaginal cancer. There seemed to be a survival advantage that was temporally related to the advent of chemo radiation.…”
Section: Journal Of Universal Surgery Issn 2254-6758mentioning
confidence: 99%